Pengaruh Woman On Board Of Commisioners, Woman On Board Of Directors, Ukuran Perusahaan Dan Koneksi Politik Dalam Memprediksi Kebangkrutan Perusahaan Sub Sektor Pertanian Yang Terdaftar Di Bursa Efek Indonesia Periode (2020-2023) - Arifin Kurniawan, Muhammad; Saraswati, w; Yudea, Yudea (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study aims to examine the effect of Woman On Board Of Commissioners, Woman On Board Of Directors, Company Size and Political Connections on Corporate Bankruptcy. The data used in this study are the annual financial reports of agricultural sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. This type of research is quantitative research. The sampling technique in this study used purposive sampling method and resulted in 38 company samples with the total sample data obtained 118 samples from 4 years of research. The research data analysis method used is descriptive statistical analysis and multiple linear regression analysis. With the test tools used are the classic assumption test, the coefficient of determination (R2) test, the F test, and the t test. The results showed that women on board of commissioners, women on board of directors and political connections had a significant and negative effect on corporate bankruptcy. As for company size, it has a significant and positive effect on corporate bankruptcy. Researchers suggest for further research to be able to increase the research sample and to be able to add or change independent variables that have not been analyzed in this study.